2018
DOI: 10.18393/ejss.384515
|View full text |Cite
|
Sign up to set email alerts
|

Can arbuscular mycorrhiza fungi and NPK fertilizer suppress nematodes and improve tuber yield of yam (Dioscorea rotundata ‘cv’ ewuru)?

Abstract: Article InfoPoor soil fertility and nematodes limit yam tuber yield and quality. Arbuscular mycorrhizal fungi (AMF) and fertilizers may suppress nematodes and improve yam productivity. We evaluated the extent AMF and fertilizer suppressed nematodes and improved yam performance. Tuber weight, mycorrhizal colonization of roots and nematode populations were evaluated with eight treatments; Control (No amendments), 90-50-75, kg N-P2O5-K2O ha -1 (NPK), (AMF) (2g/kg soil), nematodes (5000 juvenile/pot), and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In the same vein, application of NPK at 200, 400 and 600 kg ha -1 600 also had a significant lower population densities of M. incognita, H. multicinctus, P. coffeae and R. similis. Our findings were consistent with earlier studies that the use of appropriate levels of NPK fertilizers have good effects on plant growth factors with resultant reductions in plant-parasitic nematode populations (Irshad et al, 2006;Ameen et al, 2013;Osman et al, 2015;Kolawole et al, 2018). Contrarily, nematode populations were reported to have increased due to NPK and manure combined with chemical fertilizer (Hu et al, 2018).…”
Section: Effects Of Organic Fertilizers On Population Densities Of Plsupporting
confidence: 92%
“…In the same vein, application of NPK at 200, 400 and 600 kg ha -1 600 also had a significant lower population densities of M. incognita, H. multicinctus, P. coffeae and R. similis. Our findings were consistent with earlier studies that the use of appropriate levels of NPK fertilizers have good effects on plant growth factors with resultant reductions in plant-parasitic nematode populations (Irshad et al, 2006;Ameen et al, 2013;Osman et al, 2015;Kolawole et al, 2018). Contrarily, nematode populations were reported to have increased due to NPK and manure combined with chemical fertilizer (Hu et al, 2018).…”
Section: Effects Of Organic Fertilizers On Population Densities Of Plsupporting
confidence: 92%
“…This disagrees with the findings of Okae-Anti et al [18] where the resulting increase in nematode population caused a decrease in the yield of plantain. On the contrary, Kolawole et al [25] reported that NPK fertilizer significantly reduced root-knot nematode populations in the roots, soil, and on the tuber of yam, however, the nematodes increase did not reduce yam tuber weight, but reduced its quality. Table 3 recorded that season of planting was highly significant on grain yield and population of Pratylenchus brachyurus.…”
Section: Resultsmentioning
confidence: 94%
“…It is important to highlight that plants associated with AMF are more robust, as these fungi enhance nutrient and water absorption, making these plants better nourished and vigorous and thus better equipped to withstand the presence of the pathogen (Kolawole et al 2018;Campos 2020). Table 10.1 summarizes the effects on AMF, Meloidogyne, and plant parameters in experiments with AMF and Meloidogyne.…”
Section: Introductionmentioning
confidence: 99%